2022
DOI: 10.3389/fenvs.2022.1010534
|View full text |Cite
|
Sign up to set email alerts
|

Testing the impact of external sovereign debt on Turkey’s ecological footprint: New evidence from the bootstrap ARDL approach

Abstract: As is glaringly apparent, the world is now bedeviled with environmental challenges and ecological complications. This may not be unconnected with the persistent ecological challenges emanating from fossil fuel consumption and changing lifestyles. This is why various attempts are ongoing to advance the course of renewable energy and economic growth as a response to environmental change. Therefore, this study seeks to investigate the dynamic effect of external debt, energy usage, and real income on the ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Likewise, Akam et al (2022) used the AMG method and confirmed the CO2-emitting effect of external debt in South Africa and Algeria. Also, Xu et al (2022) applied the bootstrap ARDL and submitted that foreign debt is significant for enhancing Turkey's EFP quality. Samour and Adebayo (2022) demonstrated with the MMQR, CCEMG, and AMG methods that foreign debt worsened LCF in BRICS countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, Akam et al (2022) used the AMG method and confirmed the CO2-emitting effect of external debt in South Africa and Algeria. Also, Xu et al (2022) applied the bootstrap ARDL and submitted that foreign debt is significant for enhancing Turkey's EFP quality. Samour and Adebayo (2022) demonstrated with the MMQR, CCEMG, and AMG methods that foreign debt worsened LCF in BRICS countries.…”
Section: Literature Reviewmentioning
confidence: 99%